Assessing trade in the mercantilist era: evidence from a new database on foreign trade of Sweden – Finland, 1738–1805. Issue 3 (2nd September 2018) - Edvinsson, Rodney; Gad, Christoffer Tarek
ABSTRACT: This paper presents a newly constructed database on foreign trade of Sweden–Finland 1738–1805, consisting of all exports and imports that were recorded by the custom houses in this period, and is made available atwww.historia.se/Swedish foreign trade 1738_1805.xlsx . The traditional view as presented by Eli Heckscher, who was very critical of the mercantilist policies of the time, was that the overseas trade of Sweden-Finland saw a trend of secular stagnation during the course of the eighteenth century. By contrast, we show that in conjunction with a substantial expansion of the population, total trade nearly increased twofold during the period of study. Despite that, there was a small decrease in the value of exports in relation to GDP, mostly explained by a drop in the relative price of bar iron. The degree of specialisation of Swedish exports saw a declining tendency in this period. While exports from Sweden had a higher degree of specialisation than Finnish exports, imported goods to Finland were more concentrated than Swedish imports. Lastly, the composition of imports did not markedly alter, meaning that a consumer revolution did not take place in either Sweden or Finland.